A Backstepping Sliding Mode Control for a Hydrostatic Transmission with Unknown Disturbances. Issue 18 (2016) - Sun, Hao; Aschemann, Harald
Abstract: A robust backstepping control via second-order sliding mode for the speed tracking control of a hydrostatic transmission is presented in this paper. The proposed approach consists of a stabilising control action designed according to backstepping control techniques and a robust control term using a second-order sliding mode (SOSMC) approach, which is introduced to counteract the impact of uncertain system parameters as well as unknown disturbances. For the control implementation on a test bench of a hydrostatic transmission, to estimate unmeasurable system states and two lumped disturbances present in the system, the proposed controller is extended with a sliding mode observer. Both simulations and experimental results highlight the applicability of the proposed method.